Chlorine migration mechanisms during torrefaction of fermentation residue from food waste. (January 2019) - Wang, Yazhuo; Hu, Shuangqing; Li, Wenjian; Gu, Jing; Yuan, Haoran; Ling, Xiang; Chen, Yong
Highlights: Chlorine migration mechanisms of FRFW were investigated during torrefaction. Absolute content of Cl in torrefied solid products decreased. Some soluble Cl in torrefied solid products was transferred to insoluble Cl. Most of reduced Cl in FRFW was present in torrefied liquid products. Abstract: Fermentation residue from food waster (FRFW) has a large amount of residual chlorine (Cl), and the high-salt of FRFW is either landfilled or treated as a fertilizer. The transfer of chlorine to the atmosphere and soil can cause pollution and soil salinization. This work primarily investigated the combined forms and migration mechanisms of Cl during the torrefaction of FRFW from 250 to 400 °C. The results showed that the form and amount of Cl released during the torrefaction of FRFW depended on temperature. The absolute content of soluble Cl and total Cl in torrefied solid products decreased, and the absolute content of insoluble Cl reached a maximum at 350 °C, which indicated that some soluble Cl was transferred to the insoluble Cl (CCl forms). The Cl-containing products in non-condensable gas was too little to be detected, so the majority of the reduced Cl was in liquids with different organic compounds.